Designing Silica‐Based Hybrid Polymers and Their Application in the Loading and Release of Fluorescein as a Model Drug and Diagnostic Agent. Issue 2 (29th February 2016) - Jamwal, Hem Suman; Chauhan, Ghanshyam S.
ABSTRACT: Polymeric hybrid materials are interesting functional materials with many diverse properties. Two new hybrid nanomaterials, poly(methacrylic acid‐ co ‐(2‐dimethylamino)ethyl methacrylate)/silica (P(MAA‐DMAEM)/SiO2 ) and poly(methacrylic acid)/silica (P(MAA)/SiO2 ) were prepared via the emulsifier‐free emulsion polymerization in which 3‐aminopropyltriethoxysilane was used as a silane‐coupling agent, tetraethoxysilane and polyvinyl alcohol were used as a silica component precursor and polymeric colloid stabilizer, respectively. The synthesized nanomaterials were characterized by various techniques and were used as drug delivery systems. Fluorescein, mainly used in angiography, was chosen as a candidate drug/diagnostic agent to investigate its loading and release behavior from the hybrid nanomaterials. The uptake studies were carried out at room temperature, whereas the release studies were carried out at 37ºC under phosphate buffer solution at pH 7.4. The release kinetics was studied by subjecting the obtained data to different kinetic models. The nanohybrid materials exhibited a structure–property relationship in the uptake and release of fluorescein as higher adsorption capacity was observed with a P(MAA)/SiO2 hybrid nanomaterial, whereas more drug release was observed from a P(MAA‐DMAEM)/SiO2 nanomaterial than the former.